Screening for diabetes: what do the results of the ADDITION trial mean for clinical practice?. (September 2013) - Lauritzen, Torsten; Borch-Johnsen, Knut; Davies, Melanie J; Khunti, Kamlesh; Rutten, Guy EHM; Sandbæk, Annelli; Simmons, Rebecca K; van den Donk, Maureen; Wareham, Nicholas J; Griffin, Simon J
SUMMARY The main ADDITION study was planned as a screening study followed by a randomized, intervention study comparing routine treatment with more intensive treatment in people with screen-detected diabetes. The stepwise screening programs had low yield, but for each person with diabetes identified, another two at high risk of diabetes and six at high risk of cardiovascular disease were identified. Screening for diabetes had limited short- and long-term adverse psychological impacts on participants. The intervention study showed substantial improvements in cardiovascular risk factors following detection of diabetes, even among those receiving routine general practice care. The randomized trial did not deliver conclusive evidence to justify implementation of a systematic screening program. Uncertainties remain concerning the overall cost–effectiveness. However, the overall results of the ADDITION study, including cohort analyses, suggest that earlier detection and treatment of diabetes is associated with net benefits. Thus, primary care teams are encouraged to develop systems to enable earlier detection. This might include opportunistic screening. Individuals identified should be offered lifestyle interventions and preventive drug treatments appropriate to their level of risk.